Curcumin Affects Adipose Tissue-Derived Mesenchymal Stem Cell Aging Through TERT Gene Expression - Pirmoradi, Samaneh; Fathi, Ezzatollah; Farahzadi, Raheleh; Pilehvar-Soltanahmadi, Younes; Zarghami, Nosratollah (Drug Research, 2018)
Aging and losing cell survival is one of the main problems in cell therapy. Aging of Mesenchymal Stem Cells (MSCs) is associated with a rise in intracellular reactive oxygen species, decrease in telomerase reverse transcriptase (TERT) expression and finally eroded telomere ends. Given that the production of free radicals in the aging process is effective, the use of antioxidants can help in scavenging free radicals and prevent the aging of cells. The aim of this study is to evaluate the effects of curcumin on proliferation, aging and TERT expression of rat adipose tissue-derived stem cells (rADSC). rADSCs were isolated from inguinal rat adipose tissue and their viabilities were assessed by MTT after exposure to different concentrations of curcumin. Flow-cytometry was performed for investigating the cell surface markers. Adipogenic and osteogenic differentiation were carried out to evaluate the pluripotency of rADSCs. Telomerase expression and percentage of senescent cells were evaluated using real-time PCR and senescence-associated β-galactosidase activity, respectively. The results demonstrated significant proliferation of rADSCs after 48 h treatment with 1 and 5 µM curcumin. Additionally, these concentrations could significantly reduce the population doubling time and aging of rADSCs at different passages. The findings of SA-ß-gal staining showed that curcumin significantly decreased the number of senescent cells in the 5 and 7 cell passages. Moreover, expression levels of TERT increased in the presence of 1 and 5 µM curcumin than control group (P<0.001). As a conclusion, curcumin may be a good candidate to improve lifespan of rADSCs through promoting TERT gene expression.
Keywords: Curcumin; aging; TERT expression; antioxidant; rADSCs